POTENSI PEMBELAJARAN IPAS DALAM MEMPERKENALKAN KEARIFAN LOKAL DI SEKOLAH DASAR - Margaretha Lidya Sumarni; Siprianus Jewarut; Felisitas Viktoria Melati; Benedhikta Kikky Vuspitasari; Yeremia Niaga Atlantika; Maria Angela Siokalang (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The implementation of the Independent Curriculum, which integrates science and social studies into the science subject, aims to create a comprehensive understanding of science. However, the rapid flow of globalization has triggered the urgency of preserving local wisdom values ​​in national education. This study aims to instill the potential and learning strategies of science as an effective means of introducing local culture in elementary schools. Using a qualitative descriptive approach through a literature study method, this study examines various scientific sources through four systematic stages: data collection, authoritative source collection, content analysis, and comprehensive conclusions. The research findings reveal that the integration of local wisdom of the Dayak Tribe in Bengkayang Regency, such as the ethnobotanical practice of medicinal plants and traditional agricultural rituals, into the science curriculum has great potential to increase the connection of the material with the real life reality of students. The results of the literature synthesis confirm its high effectiveness with a success rate of up to 97.41% in increasing students' learning interest and critical thinking skills compared to the use of conventional methods. The main conclusion confirms that science is a pedagogical strategy medium for strengthening cultural identity while realizing the Pancasila Student Profile with ecological and religious characteristics. The success of this implementation fosters active collaboration between schools, traditional leaders, and the government in developing a contextual curriculum to ensure traditional knowledge remains sustainable for future generations. ABSTRAK Implementasi Kurikulum Merdeka yang mengintegrasikan IPA dan IPS menjadi mata pelajaran IPAS bertujuan untuk menciptakan pemahaman sains yang utuh, namun derasnya arus globalisasi memicu urgensi pelestarian nilai kearifan lokal dalam dunia pendidikan nasional. Penelitian ini bertujuan untuk mengevaluasi potensi dan strategi pembelajaran IPAS sebagai sarana efektif untuk memperkenalkan budaya lokal di jenjang sekolah dasar. Dengan menggunakan pendekatan kualitatif deskriptif melalui metode studi pustaka atau literatur, penelitian ini menelaah berbagai sumber ilmiah melalui empat tahapan sistematis yang meliputi pengumpulan data, identifikasi sumber otoritatif, analisis konten, serta penarikan kesimpulan secara komprehensif. Temuan penelitian mengungkapkan bahwa integrasi kearifan lokal Suku Dayak di Kabupaten Bengkayang, seperti praktik etnobotani tanaman obat dan ritual pertanian tradisional, ke dalam kurikulum IPAS berpotensi besar meningkatkan keterkaitan materi dengan realitas kehidupan nyata peserta didik. Hasil sintesis literatur mengonfirmasi adanya efektivitas tinggi dengan persentase keberhasilan hingga 97,41% dalam meningkatkan minat belajar serta keterampilan berpikir kritis siswa dibandingkan penggunaan metode konvensional. Simpulan utama menegaskan bahwa IPAS merupakan media pedagogis strategis untuk memperkuat identitas budaya sekaligus mewujudkan Profil Pelajar Pancasila yang berkarakter ekologis dan religius. Keberhasilan implementasi ini menuntut kolaborasi aktif antara pihak sekolah, tokoh adat, dan pemerintah dalam penyusunan kurikulum kontekstual agar pengetahuan tradisional tetap lestari bagi generasi masa depan.